Clinical course of SARS‐CoV‐2 infection and recovery in lung transplant recipients. Issue 6 (8th November 2022) - Trindade, Anil J.; Chapin, Kaitlyn C.; Gannon, Whitney D.; Hoy, Haley; Demarest, Caitlin T.; Lambright, Eric S.; McPherson, Katie A.; Norfolk, Stephanie G.; Robbins, Ivan M.; Bacchetta, Matthew; Erasmus, David B.; Shaver, Ciara M.
Abstract: Background: Reports on outcomes following severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection in lung transplant recipients remain limited. Methods: We performed a single‐center, observational study of outcomes in lung transplant recipients diagnosed with SARS‐CoV‐2 between 5/1/2020 and 3/15/2022 that were followed for a median of 123 days. We analyzed changes in spirometry, acute lung allograft dysfunction (ALAD) incidence, hospitalization, mechanical ventilation needs, secondary infection, and survival. Results: In our cohort of 336 patients, 103 developed coronavirus disease (COVID) (27 pre‐Delta, 20 Delta, and 56 Omicron‐era). Twenty‐five patients (24%) required hospitalization and 10 patients ultimately died (10%). Among 85 survivors who completed ambulatory spirometry, COVID‐19 did not alter change in forced expiratory volume in 1 s (FEV1 ) or forced vital capacity (FVC) over time compared to the preceding 6 months. The pre‐COVID FEV1 change was −0.05 ml/day (IQR −0.50 to 0.60) compared to −0.20 ml/day (IQR −1.40 to 0.70) post‐COVID ( p = .16). The pre‐COVID change in FVC was 0.20 ml/day (IQR −0.60 to 0.70) compared to 0.05 ml/day (IQR −1.00 to 1.10) post‐COVID ( p = .76). Although the cohort overall had stable lung function, 33 patients (39%) developed ALAD or accelerated chronic lung allograft dysfunction (FEV1 decline >10% from pre‐COVID baseline). Nine patients (35%) with ALAD recovered lung function. Within 3 months of acute COVID infection, 18 patients (17%) developed secondary infections, the majority being bacterial pneumonia. Finally, vaccination with at least two doses of mRNA vaccine was not associated with improved outcomes. Conclusions: This study describes the natural history of SARS‐CoV‐2 infection in a large cohort of lung transplant recipients. Although one third of patients develop ALAD requiring augmented immunosuppression, infection with SARS‐CoV‐2 is not associated with worsening lung function. Abstract :